The Effect of Infant Massage on Infant Growth and Development at the Bonggo II Community Health Center - Ni Kadek Dewi Ratih; Retno Dewi Prisusanti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
This study aimed to analyze the effect of infant massage on growth and development among infants attending Puskesmas Bongo II. Infant massage is recognized as a form of sensory stimulation that enhances neural function, improves blood circulation, and strengthens maternal–infant bonding, thereby potentially supporting optimal physical growth and developmental progress. This research employed an analytic cross-sectional design involving infants aged 0–12 months, with a total sample of 50 infants selected using purposive sampling based on predefined inclusion criteria. Information regarding infant massage practices was collected through structured maternal interviews and categorized into routine massage (≥3 times per week) and non-routine massage. Infant growth was assessed using the weight-for-age (W/A) indicator based on WHO growth standards, while development was measured using the Developmental Pre-Screening Questionnaire (KPSP). Data were analyzed using the chi-square test with a 95% confidence level (p < 0.05). The results showed that infants who received routine massage demonstrated significantly better growth status and developmental outcomes compared to those who did not receive massage routinely. These findings suggest that infant massage is a simple, safe, and practical intervention that can be recommended to support growth and development and may be integrated into maternal and child health services at Puskesmas Bongo II.